Patient safety culture: Insights from a cross-sectional study among healthcare professionals - Vijay K. Tadia; Neelam Kotwal; Rahul S. Jalaunia (Journal of Family Medicine and Primary Care)
Introduction: The classical definition of patient safety given by the IOM is, “the prevention of harm to patients.” To expect error less performance from human beings working in a complex, highly challenging, and stressful health care environment is unrealistic. The emphasis must be on fostering a culture of safety that involves multiple stakeholders including healthcare workers, healthcare organizations, and patients. Aim: To assess the culture of patient safety among healthcare professionals. Settings and Design: A descriptive cross-sectional study was conducted using a pre-validated survey instrument in a tertiary care pediatric hospital. Methods and Material: The data were collected over a period of 1 month (from 4th January 2022 to 5th February 2022) using pre-validated questionnaire based on “Surveys on Patient Safety Culture™ (SOPS™) Hospital Survey Version 2.0 (SOPS Hospital Survey 2.0)”. Both web-based and paper-based questionnaire forms were distributed among the health care workers. Results: Totally, 61% of the respondents had average positive response to patient safety, 75% positive response about communication of patient safety error and 74% about teamwork in crisis. A total of 74% responded that supervisors or clinical leaders support them in pursuit of patient safety, 73% about proper handovers. About 69% mentioned about a culture of organizational learning and continuous improvement, 59% reported any patient safety event, 49% believed in support from Hospital management and 42% believed that if a patient safety error is reported it is responded to positively by the seniors by taking corrective measures. Conclusions: The study presented with a plethora of outcomes that can be used for promoting safe healthcare. A policy for continuous improvement should be implemented to ensure the culture of safe and sustainable patient care.